Concerning violence nine scenes from the anti-imperialistic self-defense - Fanon, Frantz 1925-1961 (Dogwoof, 2015)
In this potent, arresting, and surprisingly emotional film, Olsson artfully elucidates Fanon's psychiatric and psychological analysis of dehumanizing effects of colonization on the individual and the nation. Fanon's theory is that the violence of colonialism must be met with greater violence to be defeated, as well as his vision and plea to reject the lust for colonial power and instead embrace a more creative and human society
Bildformat 16:9
Orig.: Schweden, Dänemark, Finnland, USA 2014
Enth. Spivak preface ; director's q & a with Sara Myers ; boycott zhe human zoo
Keywords: Fanon, Frantz -- 1925-1961; Geschichte 1945-1962; Decolonization; Violence; Foreign films; Geschichte; Kolonie; Kolonialismus; Entkolonialisierung; Gewalt; Algeria / History / 1945-1962; France / Colonies / Africa; Afrika; Algerien; Frankreich; DVD-Video